The New National Collegiate Athletic Association Wrestling Weight Certification Program and sport-seasonal changes in body composition of college wrestlers - Utter, A. C. (The Journal of Strength and Conditioning Research, 2001)
Changes in body composition of college-age wrestlers (N = 21, 19.0 ± 0.2 years of age, 8.2 ± 0.6 years of experience) were studied throughout the season after implementation of the new National Collegiate Athletic Association (NCAA) wrestling weight certification (WWC) program. Wrestlers were divided into 2 groups, starters (n = 10) and nonstarters (n = 11), based on the number of completed matches during the 1998-1999 season. Body density was measured via hydrostatic weighing, with residual volume determined via the nitrogen washout technique. Hydration was assessed by measuring specific gravity of urine (Usg). For body mass and fat-free mass (FFM), a significant difference in the pattern of change was found (p < 0.05), highlighted by a decrease in body mass (3.0%, 2.5 kg, 5.8 lb) and a maintenance of FFM from preseason to peak season for the starters. The pattern of change over time was significantly different for refractometry Usg (p < 0.01) but not for the test strip Usg (p = 0.54). No significant interaction effects were seen for percentage of body fat or fat mass. Significant time main effects were found for percentage of body fat, body mass, fat mass, FFM, and refractometry Usg. Taken together, the results of this investigation demonstrate that collegiate wrestlers lose body mass but maintain FFM throughout the season, which may in part be associated with the new NCAA WWC program.